Conceptualization of ocean development: The evolution of the law and the naval strategy for sustainability (Revista da EGN, 2023)
Taking into consideration the radical changes concerningdevelopment in the past century, this work has been for-mulated to see a new perspective where the ocean can berevived as a fundamental player for sustainable growthand development today. Structured in three sections, thispaper goes through the geographers’ vision of the oceanas an original and rediscovered space of society, followedby juridical thought and its application to internationalocean governance. That culminates with the capacity tosystematically consolidate the different aspects of the mi-litary navies and how the navy can be reorganised to fitthe reality of ocean sustainability and development.